If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + 6 + -12 = -30 Reorder the terms: 6 + -12 + -8x = -30 Combine like terms: 6 + -12 = -6 -6 + -8x = -30 Solving -6 + -8x = -30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -8x = -30 + 6 Combine like terms: -6 + 6 = 0 0 + -8x = -30 + 6 -8x = -30 + 6 Combine like terms: -30 + 6 = -24 -8x = -24 Divide each side by '-8'. x = 3 Simplifying x = 3
| 6x+21=x+7 | | 12+4x-x=x+28 | | 5x+28.0=58.0 | | 2b-31/3=11/3 | | (x+5)=(3x-2) | | 11/30x360 | | 7x^2+8xy+y^2=45 | | (5v-9)(8-v)=0 | | ((12v^6)-(14v^3))/(2v^3) | | 2mx^2+3mx=0 | | 2(4x-3)=58 | | 2(x-2)+3x=6x+7-(x-3) | | 15x-220=5x-10 | | 16-11x+12=-16x | | -2x-7+3x=2(5x-9) | | 3e/(e^x) | | 159*200000/X=8.50 | | 2-55m-5=73 | | 32x+48=11-x-7 | | 2(3x-5)=2x-1 | | (2n+6)(4n+2)+16=80 | | 2n^2-40=-11n | | 8n+1=13+2n+8n | | V^2-2vf+f^2=0 | | 3=7cos(2x) | | 3-18x-6=3 | | y=7cos(2x) | | 175+2(100)= | | 9x-124=3x-10 | | 3(2x+5)+3x=42 | | 5(3x-4)-6x=4x+8 | | (7t+6)+(3t+x)+(4t+y)=48 |